A systematic review and meta-analysis of combined carotid endarterectomy with ipsilateral proximal intervention (hybrid approach) for tandem carotid artery lesions - Qi, Wanting; Lai, Zhichao; Shao, Jiang; Li, Kang; Fang, Lijing; Xu, Leyin; Zhang, Xin; Liu, Bao (Journal of vascular surgery, 2021)
The safety and effectiveness of using the hybrid approach to treat tandem carotid lesions is controversial, and the clinical significance of the technical variants on the perioperative outcomes has not been evaluated. The present meta-analysis was performed to evaluate the technique, safety, effectiveness, and long-term outcomes of the hybrid approach. The PubMed, Embase, and Cochrane Library databases were searched to identify studies from January 1, 1996 to January 11, 2020. The baseline patient characteristics, comorbidities, procedural details, and perioperative and long-term outcomes were collected and analyzed. A pooled overall survival curve was drawn. Univariate analysis was performed to compare the perioperative stroke risk between subgroups. Overall, 275 patients (mean age, 66.94 years) from 15 studies were included. All the patients had presented with tandem stenosis of ≥50%, and 67.2% were symptomatic. The overall technical success rate was 99.8% (95% confidence interval [CI], 98.0%-100.0%). The pooled perioperative complications rates were as follows: death, 1.5% (95% CI, 0.0%-2.9%); stroke, 2.6% (95% CI, 0.7%-4.4%); combined stroke/death, 3.3% (95% CI, 1.2%-5.4%); and myocardial infarction, 3.2% (95% CI, 0.7%-9.1%). The overall primary patency rates were 99.2% (95% CI, 96.0%-100.0%) and 88.2% (95% CI, 78.8%-95.4%) at 1 and 2 years, respectively. Reintervention was performed in 6.6% of the patients (95% CI, 3.0%-11.2%). The pooled overall survival rates were 89.9% (95% CI, 83.7%-96.7%), 83.7% (95% CI, 75.9%-92.2%), and 75.9% (95% CI, 66.5%-86.7%) at 1, 3, and 5 years, respectively. Operations in which carotid endarterectomy was performed first carried a significantly greater risk of perioperative stroke compared with those in which proximal intervention had been performed first (5.7% vs 0.0%; P = .01). No difference was found in perioperative stroke risk between the subgroups of baseline symptomatic status (asymptomatic, 5.1%; symptomatic, 1.9%; P = .32), preoperative antiplatelet therapy (dual, 3.6%; single, 5.8%; P = .79), and carotid clamping during intervention (clamping, 2.8%; unclamping, 6.3%; P = .40). For patients with a presumed high risk of neurologic events because of carotid tandem lesions, the hybrid approach could be considered a reasonable option with high technical success and acceptable perioperative and long-term results. Performing carotid artery stenting before carotid endarterectomy and administering perioperative dual antiplatelet therapy should be considered to promote technical success and better outcomes. Prospective and randomized controlled studies are needed to confirm the results and provide recommendations on patient selection for the hybrid approach.